(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Jammu is a fast-growing and major city in northern India, in UT Jammu & Kashmir. Jammu, the winter capital, is a city of temples, a symbol of ancient values, and has a distinct image due to its legacy, geography, and connections. The present study focuses on Site Characterization through geophysical testing i.e., (Active) Multi-channel Analysis of Surface Waves. Multi channel analysis of surface wave (MASW) is used for measuring the shear wave velocity (VS) at twenty-one (21) locations within Jammu city using TROMINO. Shear Wave velocity profiles over 30 m depth have been generated at each location using Grilla Software. Using the VS30 values seismic site characterization of the locations has been carried according to National Earthquake Hazard Reduction Program (NEHRP) guidelines. VS30 is a significant input for evaluating the seismic response of a soil deposit to earthquakes because it is a dynamic property of soils. The value of VS30 for the sites is varying from 271 m/s to 475 m/s. Site characterization revealed that most of the sites fall under C and D categories. From the VS30 values further a map was generated using a GIS platform that can be used for hazard estimation.